Effects of music therapy under general anesthesia in patients undergoing abdominal surgery. Issue 1 (1st January 2017) - Kahloul, Mohamed; Mhamdi, Salah; Nakhli, Mohamed Said; Sfeyhi, Ahmed Nadhir; Azzaza, Mohamed; Chaouch, Ajmi; Naija, Walid
ABSTRACT: Background : Music therapy, an innovative approach that has proven effectiveness in many medical conditions, seems beneficial also in managing surgical patients. The aim of this study is to evaluate its effects, under general anesthesia, on perioperative patient satisfaction, stress, pain, and awareness. Methods : This is a prospective, randomized, double-blind study conducted in the operating theatre of visceral surgery at Sahloul Teaching Hospital over a period of 4 months. Patients aged more than 18 undergoing a scheduled surgery under general anesthesia were included. Patients undergoing urgent surgery or presenting hearing or cognitive disorders were excluded. Before induction, patients wore headphones linked to an MP3 player. They were randomly allocated into 2 groups: Group M (with music during surgery) and group C (without music). Hemodynamic parameters, quality of arousal, pain experienced, patient's satisfaction, and awareness incidence during anesthesia were recorded. Results : One hundred and forty patients were included and allocated into 2 groups that were comparable in demographic characteristics, surgical intervention type and anesthesia duration. Comparison of these two groups regarding the hemodynamic profile found more stability in group M for systolic arterial blood pressure. A calm recovery was more often noted in group M (77.1% versus 44%, p < 10 –3 ). The average Visual Analog Scale (VAS) score was lower in the intervention group (33.8 ± 13.63 versus 45.1 ± 16.2; p < 10 –3 ). The satisfaction rate was significantly higher among the experimental group (81.4% versus 51.4%; p < 10 –3 ). The incidence of intraoperative awareness was higher in group C (8 cases versus 3 cases) but the difference was not statistically significant. Conclusion : Music therapy is a non-pharmacological, inexpensive, and non-invasive technique that can significantly enhance patient satisfaction and decrease patients' embarrassing experiences related to perioperative stress, pain, and awareness.